The thalamostriatal system in normal and diseased states - Smith, Yoland; Galvan, Adriana; Ellender, Tommas J.; Doig, Natalie; Villalba, Rosa M.; Ocampo, Icnelia H.; Wichman, Thomas; Bolam, Paul (Frontiers in Systems Neuroscience, 2014)
Because of our limited knowledge of the functional role of the thalamostriatal system, this massive network is often ignored in models of the pathophysiology of brain disorders of basal ganglia origin, such as Parkinson’s disease. However, over the past decade, significant advances have led to a deeper understanding of the anatomical, electrophysiological, behavioral and pathological aspects of the thalamostriatal system. The cloning of the vesicular glutamate transporters 1 and 2 (vGluT1 and vGluT2) has provided powerful tools to differentiate thalamostriatal from corticostriatal glutamatergic terminals, allowing us to carry out comparative studies of the synaptology and plasticity of these two systems in normal and pathological conditions. Findings from these studies have led to the recognition of two thalamostriatal systems, based on their differential origin from the caudal intralaminar nuclear group, the centre median/parafascicular (CM/Pf) complex, or other thalamic nuclei. The recent use of optogenetic methods supports this model of the organization of the thalamostriatal systems, showing differences in functionality and glutamate receptor localization at thalamostriatal synapses from Pf and other thalamic nuclei. At the functional level, evidence largely gathered from thalamic recordings in awake monkeys strongly suggests that the thalamostriatal system from the CM/Pf is involved in regulating alertness and switching behaviors. Importantly, there is evidence that the caudal intralaminar nuclei and their axonal projections to the striatum partly degenerate in Parkinson’s disease and that CM/Pf deep brain stimulation may be therapeutically useful in several movement disorders.